A tale of two trade regimes: India's development experience - Matthias Oschinski (Transformation, Integration and Globalization Economic Research (TIGER), 2005)
When India initiated economic reforms in July 1991 to deal with the consequences of the balance of payments crisis the country also started to open its economy to international trade - if only gradually. Over the years, this policy has been criticized by NGOs as harming the poor through increased competition by multinational companies and through declining prices of agricultural products. Consequently, this paper analyses India's performance with regard to its two different trade regimes over the past four decades and assesses their respective impacts on poverty alleviation.
Keywords: 330; Außenwirtschaftspolitik; Handelsliberalisierung; Wirkungsanalyse; Armut; Indien